Brer Rabbit: story collection - Blyton, Enid (Hodder Children's Books London, 2016)
It's wits against brawn in the classic tales of Brer Rabbit, re-told by one of the world's best-loved children's authors, Enid Blyton. Brer Rabbit is as clever as can be. He loves to play jokes and tricks on his animal friends, but every now and then they get him back! Join Brer Rabbit, Brer Fox and Brer Bear in over 80 short stories re-told by Enid Blyton for children in her own style. This collection contains stories from the books Enid Blyton's Brer Rabbit Book (1948), Brer Rabbit Again (1963) and Brer Rabbit's a Rascal! (1965) and black and white illustrations